The European Union as a Community of Values: the Importance of the Dialogue between the Court of Justice of the European Union and National Courts - Jarukaitis, Irmantas (Teisė, 2024)
The article deals with the gradual development of the EU as a community of values and the role of the CJEU and national courts in upholding and developing these values. The analysis of judicial practice reveals the crucial role performed by national courts and the CJEU in protecting the fundamental rights and the principle of the rule of law both at the EU and national levels. On the one hand, „upstream“, national courts act as guardians of the fundamental values at the EU level by referring questions to the CJEU concerning the interpretation of the Charter and the legality of the secondary EU legislation vis-à-vis the Charter, thus contributing to the functioning of a decentralised constitutional control of EU legislation and stabilising the EU level of governance. On the other hand, “downstream”, recent developments of the CJEU jurisprudence interpreting Article 19 of the Treaty on the European Union confirm the thesis that the CJEU treats national courts as European courts that are cornerstones of the decentralised EU judicial system. The CJEU practice shows that differently from Article 47 of the Charter, Article 19 of the TEU is perceived not as providing protection of individual rights but rather as a systemic and permanent guarantee of judicial independence as a part of a fundamental value of the Union, thus aiming at stabilisation of national judicial systems and assuring the effectiveness of protection of the rights stemming from EU law at the national level.